Reducing the power consumption of hose‐model networks with bundled links. Issue 2 (1st March 2015) - Ba, Seydou; Ouédraogo, Ihsen Aziz; Oki, Eiji
Abstract : Given the exponential growth in telecommunication networks, more and more attention is being paid to their share in the global energy consumption. Reducing networks' power consumption has become a major concern. However, the often over‐provisioned wired core network is still overlooked. In core networks, pairs of routers are typically connected by multiple physical cables that form one logical bundled link participating in the intra‐domain routing protocol. To reduce the energy consumption of core networks with bundled cables, the authors propose a scheme to deactivate the maximum possible number of cables, and associated equipment, while considering hose‐model traffic. A similar approach has been presented for the pipe model, where the exact traffic matrix is assumed to be known. Owing to traffic uncertainty, however, it is difficult for network operators to have exact knowledge of the traffic matrix. This traffic uncertainty can be avoided by using the hose model, which specifies only the upper bounds of the egress/ingress traffic from/to a node. They introduce a mixed integer linear problem formulation that yields the optimal solution and a more practical and near optimal heuristic algorithm for large networks. The author's performance evaluation results show that it offers up to 50% power reduction.